2018
DOI: 10.1186/s40168-018-0405-8
|View full text |Cite
|
Sign up to set email alerts
|

Crawling-induced floor dust resuspension affects the microbiota of the infant breathing zone

Abstract: BackgroundFloor dust is commonly used for microbial determinations in epidemiological studies to estimate early-life indoor microbial exposures. Resuspension of floor dust and its impact on infant microbial exposure is, however, little explored. The aim of our study was to investigate how floor dust resuspension induced by an infant’s crawling motion and an adult walking affects infant inhalation exposure to microbes.ResultsWe conducted controlled chamber experiments with a simplified mechanical crawling infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…Recently, we have shown that the microbiota of floor dust are not fully consistent with the microbiota of infant breathing zone air, but the microbiota of bulk air in a room are also not fully representative of the particular infant breathing exposure on activities near the floor. 38 As noted earlier, oral ingestion exposure or exposure through the skin during the first years of life might be relevant as well. 2 One weakness of our study is that the taxonomic resolution of the sequencing approach did not, in general, allow species-level identification.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we have shown that the microbiota of floor dust are not fully consistent with the microbiota of infant breathing zone air, but the microbiota of bulk air in a room are also not fully representative of the particular infant breathing exposure on activities near the floor. 38 As noted earlier, oral ingestion exposure or exposure through the skin during the first years of life might be relevant as well. 2 One weakness of our study is that the taxonomic resolution of the sequencing approach did not, in general, allow species-level identification.…”
Section: Discussionmentioning
confidence: 98%
“…Moisture is one of the most potent contributors to microbial survival in air and on surfaces [100][101][102][103], including resistance to electrostatic charges on surfaces [104], microbial activity [86,105], and the structure of the microbial community overall as survivors prosper [34,56,106]. The ability of microbial cells or spores to become aerosolized from surfaces and be resuspended into air due to occupant traffic or disturbance [107,108] is increased by a lowrelative humidity [109]. Low-relative humidity, such as 20-30%, increases the infection rates of aerosolized particles, such as influenza [110,111], as well as overall HAI frequencies [112].…”
Section: Moisture and Relative Humiditymentioning
confidence: 99%
“…Indeed, a few studies reported microbial richness in floor dust is generally higher than richness in air dust. One school study reported fungal richness in floor dust was 1.4 times the fungal richness in air dust [16], and a crawling infant study reported that the bacterial richness (estimated by Chao1 and Shannon diversity) in the floor carpet was approximately one fold higher than the bacterial richness in infant breathing air (25 cm above ground) and two fold higher than adult breathing air (1.5 m above ground) [24]. Current microbiome analysis standard generally set same rarefaction depth for all samples within a study, and in this study the depth was set to 11,000 reads.…”
Section: Discussionmentioning
confidence: 99%